PENERAPAN TEKNIK IMAGERY TRAINING UNTUK MENGATASI INSOMNIA PADA KLIEN “N” MAHASISWA UIN RADEN FATAH PALEMBANG: PENERAPAN TEKNIK IMAGERY TRAINING UNTUK MENGATASI INSOMNIA PADA KLIEN “N” MAHASISWA UIN RADEN FATAH PALEMBANG - Nur Tasha Amelia; Suryati; Neni Noviza (Jurnal At-Taujih, 2023)
This research is entitled "Application of Image Training Techniques in Overcoming Insomnia in Clients "N" Students of UIN Raden Fatah Palembang". This study aims to determine the insomnia condition experienced by client "N" in UIN Raden Fatah Palembang students and to determine the application of imagery training techniques to overcome insomnia in client "N" in UIN Raden Fatah Palembang students. This type of research is field research with a qualitative approach and case study method. The subject of this research is one of the students of UIN Raden Fatah Palembang, namely client "N". Data collection techniques used are observation, interviews, and documentation. While data analysis techniques, pattern matching, formation of explanations and time series analysis. The results of this study indicate that the condition of client "N"'s insomnia is difficulty sleeping, feeling tired, headaches, difficulty concentrating, irritability, red eyes, and sleepiness during the day so they don't do activities. well. After carrying out the counseling process in 8 meetings using 5 stages in the application of imagery training techniques, so that results are obtained, client "N" has experienced many changes and has returned to its original state where the client is able to sleep and regulate his sleep. pattern correctly. Client "N" began to show a responsive response and concentrate fully in completing tasks and obligations. This shows a much better change in client "N" and helps clients maintain a balance of sleep patterns and health, through Imagery Training therapy to form good habits in client "N".